Intellectual currents and the practice of engagement - Beamish, David Thomas. (Piscataway, NJ)
vi, 202 sayfa
Keywords: “This book examines the French-language writings of Ottoman and Algerian writers between 1890 and 1914. The volume of engagement by these figures in the French-language intellectual and journalistic space is a historical phenomenon that reflects a particular mode of engagement with the West in the decades before the First World War. Rather than analyse these writings through the lens of their connection to particular specific groups, such as Young Turks or Young Algerians, this book aims to take this body of work as a unique category of textual production that performed a specific function. By tracing the works of a wide variety of Ottoman and Algerian writers across multiple platforms in this period, it is possible to conclude that these individuals were engaged in more than acts of political opposition. Rather, they were working to situate themselves within a specific cultural and intellectual space“ --